HOTEL AMENITIES AND THEIR IMPORTANCE ("Conference on Universal Science Research 2023", 2025)
Hotel amenities play a crucial role in enhancing guest satisfaction and influencing their decision-making process. Modern travelers expect a combination of essential and luxury amenities that contribute to their overall experience. This article explores different types of hotel amenities, their significance in guest retention, and their impact on hotel ratings. The study also highlights the growing trends in hotel amenities and their role in customer loyalty.